Population Dynamics of the Endangered Plant, Phaedranassa tunguraguae, from the Tropical Andean Hotspot - Oleas, Nora (2012)
The Tropical Andes is a diversity hotspot for plants, but there is a scant knowledge about patterns of genetic variation within its constituent species. Phaedranassa tunguraguae is an IUCN endangered plant species endemic to a single valley in the Ecuadorian Andes. We estimate the levels of genetic differentiation across the geographic distribution of P. tunguraguae using 12 microsatellite loci. We discuss factors that might influence the genetic structure of this species. Genetic distance was used to evaluate relationship among populations and geographic patterns. Bayesian methods were used to investigate population structure, migration, evidence of recent bottlenecks, and time of divergence. The 7 populations form 2 genetic clusters. These clusters show highly significant differentiation between them, along with isolation by distance. Allele richness decreases from the most diverse westernmost population to the least diverse easternmost population. The species overall shows an excess of homozygotes, with highest levels of inbreeding in the easternmost population. We found evidence of recent bottleneck events. Migration rates were in general low but were higher between populations within each of the clusters. Time of divergence between populations was related to historical volcanic activity in the area. Based on our results, we propose 2 management units for P. tunguraguae. © The American Genetic Association. 2012. All rights reserved.